Responsive vocational education to the needs of the world of work: A literature review of critical factors - Lukitasari, Febriani; Wrahatnolo, Tri; Suhartini , Ratna; Astuti, Nugrahani (Jurnal Pendidikan Teknologi Kejuruan, 2025)
This article aims to identify and analyze critical factors that influence the responsiveness of vocational education to the needs of the world of work through a systematic literature review approach to 30 international scientific articles indexed by Scopus. The results of the study indicate that the responsiveness of vocational education is largely determined by four main elements, namely: (1) strategic partnerships between vocational education institutions and the industrial world in order to align the curriculum (link and match), (2) strengthening the integration between hard skills and soft skills in graduates to face the challenges of 21st century competencies, (3) the central role of vocational educators that needs to be improved through continuous professional training, and (4) the use of innovation and learning technology such as VR (Virtual Reality), AR (Augmented Reality), and AI (Artificial Intelligence) in the vocational education process. These findings emphasize that vocational education needs to continue to adapt to the dynamics of industry and technological developments to produce competent, adaptive, and highly competitive graduates in the global job market.